Tolkāppiyariliruntu Pāratiyār varai - Civañāṉam, Ma. Po., 1906- (Iṉpa Nilaiyam, 1979)
Study of the ancient Tamil grammar Tolkappiyam by Tolkappiyar and the writings of C. Subrahmanya Bharati, 1882-1921, Tamil poet and revolutionary.